À propos d’une production céramique indigène dite matt-painted dans le cadre de l’Italie méridionale protohistorique - Clément Bellamy (Frontière·s)
This article examines the modalities of interaction between Indigenous and Greek communities in Southern Italy through the study of its ceramic productions, in particular the so-called ‘matt-painted’ indigenous pottery from Incoronata between the 8th and 7th centuries BC. We propose to question ourselves on the different levels of interactions and exchanges between indigenous and non-indigenous communities, by articulating our reflection around a necessary distinction between the context of production and the context of consumption. Networking with more recent data and excavations (Francavilla Marittima, Amastuola, Roca ...), we will read Incoronata’s archaeological contexts thanks to the contributions of multidisciplinarity, from concepts developed within anthropological sciences to technological analyzes. This will allow us to refine the reading grid of Italian protohistory, and to grasp more precisely the identity strategies of these local elites within the Mediterranean world.